2012
DOI: 10.1186/1743-422x-9-248
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of human enterovirus71 and coxsackievirusA16 in Jiangsu province, China

Abstract: BackgroundThe major etiology of hand, foot and mouth disease (HFMD) is infection with human enterovirus A (HEV-A). Among subtypes of HEV-A, coxsackievirusA16 (CoxA16) and enterovirus 71 (EV71) are major causes for recurrent HFMD among infants and children in Jiangsu Province, mainland China. Here, we analyzed maternal antibodies between prenatal women and their neonates, to determine age-specific seroprevalence of human EV71 and CoxA16 infections in infants and children aged 0 to 15 years. The results may faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 30 publications
6
39
5
Order By: Relevance
“…This was in contrast to previous studies which found decreased EV71 GMT with age [25], [37]. The steady state of EV71 immune level may attribute to lasting EV71 circulation in mainland China since the 2008.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…This was in contrast to previous studies which found decreased EV71 GMT with age [25], [37]. The steady state of EV71 immune level may attribute to lasting EV71 circulation in mainland China since the 2008.…”
Section: Discussioncontrasting
confidence: 97%
“…The proportion of positive individuals identified in our results was slightly higher than the values observed in other cities in mainland China, including Lu’an, Shanghai and Jiangsu [19], [24], [25]. The difference might be related to the geographical difference in samples tested.…”
Section: Discussioncontrasting
confidence: 84%
“…2,19 As demonstrated here, EV71 antibody decreased between 0 to 4 months, remained at a low level until 10 months, and increased to a maximum at 36 months. The overall trends were consistent with those for another investigation conducted in the same region, 24 although, in our study, the seroprevalence between 4 and 10 months fluctuated somewhat. For neonates, the positive rate was higher than that for other areas.…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the presence of maternal antibody, for there is a strong correlation of neutralizing antibody in prenatal women and neonates. 2,19,24 Moreover, the low level of EV71 neutralizing antibody in children between 5 and 6 months of age showed that they were more likely to be infected, indicating the optimal time for vaccination. Nevertheless, application of these findings into strategies to improve the efficiency of control of HFMD remains to be determined.…”
Section: Discussionmentioning
confidence: 97%
“…Our meta-analysis showed that, on average, 78% of neonates in China investigated were seropositive (Figure 3, Appendix Figure 1), somewhat higher than reported in studies conducted in Viet Nam, Thailand and Singapore (ranging from 44–67%) [61–63], suggesting a high level of maternal antibody against EV71 infection in China, perhaps due to higher historical incidence of infections among adults [17, 29, 41, 64]. In general, the titer and duration of maternal immunity of infants are associated with the level of mother’s immunity [32].…”
Section: Discussionmentioning
confidence: 69%